Investing in asset-backed securities (Frank J. Fabozzi Associates, 2000)
A collection of articles from various professionals, discussing the details of investing in asset-backed securities. Main topics addressed include non-real estate backed ABS, collateralized debt obligations, residential real-estate backed ABS, accounting, commercial mortgage backed securities, and analysis of ABS.